Valsartan induced exanthematous macular skin lesions - Che' Man, Mohamad; Che Alhadi, Shahidah; Azmi, Nurul Husna; Mohd Arifin, Siti Roshaidai; Amirruddin, Salman (EManuscript Technologies, 2020)
Valsartan is one of the antihypertensive agents under angiotensin II receptor blocker (ARB) group that commonly used in treating hypertensive patient with underlying heart failure, chronic kidney disease and angiotensin converting enzyme inhibitor (ACE-i) drug’s intolerance. We report a case of Valsartan induced exanthematous macular skin lesions. This case illustrates a rare adverse cutaneous effect of Valsartan with skin manifestation that mimicking other common skin diseases. Clinicians should consider Valsartan as one of the triggering factors for exanthematous skin manifestation.